Thermal stability of electrodeposited LIGA Ni-W alloys for high temperature MEMS applications - Haj-Taieb, M.; Haseeb, A.S. Md. Abdul; Caulfield, J.; Bade, Klaus; Aktaa, J.; Hemker, K.J. (Springer Verlag (Germany), 2008)
For thermally stable LIGA materials for high temperature MEMS applications LIGA Ni-W layers and micro testing samples with different compositions (15 and 5 at W) were electrodeposited. In order to investigate the thermal stability the Ni-W layers were annealed at different temperatures (300-700 degrees C) and for different durations (1, 4, 16 h). Their microstructure and micro-hardness were than analysed after annealing and compared with those of as-deposited states. The observed microstructures show, in comparison to pure LIGA nickel, a small grain growth and a relatively stable structure up to 700 degrees C. The micro-hardness values of the LIGA Ni-W layers are higher than those of the pure LIGA nickel. The micro-hardness measurements for high W-content show in addition a low decrease of the hardness values with increase of the annealing duration. Tensile tests were carried out for each composition (5 and 15 at). Ni-W shows higher strength (UTS) above 750 MPa and 1,000 MPa, respectively and lower ductility than pure nickel.